2021
DOI: 10.1111/1462-2920.15751
|View full text |Cite
|
Sign up to set email alerts
|

Novel Alcaligenes ammonioxydans sp. nov. from wastewater treatment sludge oxidizes ammonia to N2 with a previously unknown pathway

Abstract: Heterotrophic nitrifiers are able to oxidize and remove ammonia from nitrogen-rich wastewaters but the genetic elements of heterotrophic ammonia oxidation are poorly understood. Here, we isolated and identified a novel heterotrophic nitrifier, Alcaligenes ammonioxydans sp. nov. strain HO-1, oxidizing ammonia to hydroxylamine and ending in the production of N 2 gas. Genome analysis revealed that strain HO-1 encoded a complete denitrification pathway but lacks any genes coding for homologous to known ammonia mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 62 publications
(76 reference statements)
2
62
0
Order By: Relevance
“…The application of the traditional biological nitrogen removal process in actual wastewater treatment plants is not recommended due to high capital costs and the need for external carbon sources, aeration, and other conditions that raise treatment costs, coupled with long hydraulic retention time and high energy consumption. An innovative nitrogen removal process with high efficiency and low treatment cost has become a research hotspot for eco-environmental researchers. , The emergence of nitrogen removal reactions such as simultaneous nitrification and denitrification, anammox, , and direct ammonia oxidation (Dirammox) provides more low-cost and low-energy pathways for removing nitrogen compounds. Anammox is valued by scholars for its ability to convert NH 4 + –N as an electron donor and NO 2 – –N as an electron acceptor through anaerobic ammonia-oxidizing bacteria (AOB) into N 2 and rare NO 3 – –N under anaerobic conditions without an organic carbon source. , The partial nitrification (PN) process oxidizes NH 4 + –N to NO 2 – –N by AOB, which can be used as a pretreatment process for anammox .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of the traditional biological nitrogen removal process in actual wastewater treatment plants is not recommended due to high capital costs and the need for external carbon sources, aeration, and other conditions that raise treatment costs, coupled with long hydraulic retention time and high energy consumption. An innovative nitrogen removal process with high efficiency and low treatment cost has become a research hotspot for eco-environmental researchers. , The emergence of nitrogen removal reactions such as simultaneous nitrification and denitrification, anammox, , and direct ammonia oxidation (Dirammox) provides more low-cost and low-energy pathways for removing nitrogen compounds. Anammox is valued by scholars for its ability to convert NH 4 + –N as an electron donor and NO 2 – –N as an electron acceptor through anaerobic ammonia-oxidizing bacteria (AOB) into N 2 and rare NO 3 – –N under anaerobic conditions without an organic carbon source. , The partial nitrification (PN) process oxidizes NH 4 + –N to NO 2 – –N by AOB, which can be used as a pretreatment process for anammox .…”
Section: Introductionmentioning
confidence: 99%
“…An innovative nitrogen removal process with high efficiency and low treatment cost has become a research hotspot for eco-environmental researchers. 6,7 The emergence of nitrogen removal reactions such as simultaneous nitrification and denitrification, 8 anammox, 9,10 and direct ammonia oxidation (Dirammox) 11 provides more low-cost and low-energy pathways for removing nitrogen compounds. Anammox is valued by scholars for its ability to convert NH nitrification (PN) process oxidizes NH 4 + −N to NO 2 − −N by AOB, which can be used as a pretreatment process for anammox.…”
Section: Introductionmentioning
confidence: 99%
“…Initial testing suggested that Alcaligenes used a two-step process involving the oxidation of NH 4 + to nitrite/nitrate, followed by a reduction to N 2 [ 12 , 13 ]. However, it has been recently suggested that Alcaligenes use a previously unknown pathway to convert ammonium into N 2 (Dirammox route) [ 14 , 15 ]. According to whole genome annotation data, Alcaligenes strain HO-1 encodes a complete denitrification pathway, but it lacks genes coding for ammonia monooxygenases or hydroxylamine oxidoreductases homologs.…”
Section: Introductionmentioning
confidence: 99%
“…However, a combination of inhibition experiments and isotopic labelling suggested that strain HO-1 had a novel genetic cluster for ammonia oxidation, encoding for a previously unknown pathway able to shortcut the conventional nitrogen cycle. In the Dirammox route, NH 4 + is firstly oxidised to hydroxylamine (NH 2 OH) and then to N 2 [ 14 ]. This enzyme (encoded by the DnfA) has finally been identified and characterised by isotopic experiments.…”
Section: Introductionmentioning
confidence: 99%
“…LAD9 isolated by Chen and Ni (2012) and Alcaligenes ammonioxydans sp. HO-1 isolated by Wu et al (2021) denitrified to N 2 after transformation of NH 4 + to NO 2 − . In contrast, Pseudomonas putida Y-9 directly transformed NH 4 + to nitric oxide (NO) and then to N 2 O, and no other intermediates were found ( Huang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%